2020
DOI: 10.3892/br.2020.1282
|View full text |Cite
|
Sign up to set email alerts
|

Plasma AXIN1 expression exhibit negative correlations with inflammatory biomarkers and is associated with gastrointestinal symptoms in endometriosis

Abstract: The cytoplasmic protein AXIN1 is involved in the Wnt signalling pathway and its expression is increased in patients with endometriosis compared with healthy controls. The aim of the present cross-sectional study was to further assess the levels of AXIN1 and other inflammatory biomarkers in patients with endometriosis. Patients with laparoscopy-verified endometriosis were recruited (n=172) and completed a questionnaire regarding socioeconomic factors, lifestyle habits and medical history. Plasma AXIN1 and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…A previous study has described an association between the protein AXIN1 and endometriosis in humans [ 17 ]. The study showed that plasma levels of AXIN1 were higher in patients with current hormone treatment, positively correlated with both duration and degree of gastrointestinal symptoms, and negatively correlated with levels of fecal calprotectin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study has described an association between the protein AXIN1 and endometriosis in humans [ 17 ]. The study showed that plasma levels of AXIN1 were higher in patients with current hormone treatment, positively correlated with both duration and degree of gastrointestinal symptoms, and negatively correlated with levels of fecal calprotectin.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not find any correlation between AXIN1 levels and abundance of bacteria, which differed between those with or without gastrointestinal symptoms or hormonal treatment. The correlation between fecal calprotectin and Ruminococcus could possibly reflect more inflammation in the group treated with hormones [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, AXIN1 acts as a repressor of the Wnt signaling pathway, which is involved in cell proliferation. A negative correlation between AXIN1 and inflammatory markers in patients with endometriosis has been reported [34].…”
Section: Discussionmentioning
confidence: 94%